Amino Acid Utilization May Explain Why Bemisia tabaci Q and B Differ in Their Performance on Plants Infected by the Tomato yellow leaf curl virus - Guo, Litao; Su, Qi; Yin, Jin; Yang, Zezhong; Xie, Wen; Wang, Shaoli; Wu, Qingjun; Cui, Hongying; Zhang, Youjun (Frontiers in Physiology, 2019)
Plant-infecting viruses are well known to change host plant physiology so as to make the plants more attractive to vectors of those viruses. The recent outbreaks of Tomato yellow leaf curl virus (TYLCV) in China have been associated with the spread of its primary vector, the whiteﬂy Bemisia tabaci. Here, we determined whether the better performance of B. tabaci biotype Q than biotype B on TYLCV-infected tomato plants can be explained by differences in the ability of the two biotypes to obtain free amino acids from the virus-infected plants. We found that TYLCV infection of tomato plants significantly affected the mol% of free amino acids in the phloem sap of the tomato plants and the mol% of free amino acids in B. tabaci adults and in B. tabaci honeydew. TYLCV infection caused the mol% of a larger number of free amino acids to rise in B. tabaci Q than in B, and analysis of honeydew indicated that, when feeding on TYLCV-infected plants, B. tabaci Q was better able to use the free amino acids than B. tabaci B. The results suggest that B. tabaci Q is better adapted than B to feed on TYLCV-infected plants. The results therefore suggest that TYLCV alters the B. tabaci B–Q competitive interaction in favor of Q.